2009
DOI: 10.1111/j.1369-1600.2009.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

PRECLINICAL STUDY: Stimulation of 5‐HT1B receptors enhances cocaine reinforcement yet reduces cocaine‐seeking behavior

Abstract: Paradoxically, stimulation of 5-HT 1B receptors (5-HT 1B Rs) enhances sensitivity to the reinforcing effects of cocaine but attenuates incentive motivation for cocaine as measured using the extinction/ reinstatement model. We revisited this issue by examining the effects of a 5-HT 1B R agonist, CP94253, on cocaine reinforcement and cocaine-primed reinstatement, predicting that CP94253would enhance cocaine-seeking behavior reinstated by a low priming dose, similar to its effect on cocaine reinforcement. Rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
88
3
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(108 citation statements)
references
References 50 publications
15
88
3
2
Order By: Relevance
“…However, in apparent contrast to these effects, we found that RU24969 (Acosta et al, 2005) and CP94253 (Pentkowski et al, 2009) dose-dependently decrease cue- and cocaine-primed reinstatement of extinguished cocaine-seeking behavior. The RU24969-induced decreases in reinstatement of cocaine seeking are reversed by the antagonist GR127935, suggesting that they are 5-HT 1B R-mediated.…”
Section: Dysregulation Of 5-ht1brscontrasting
confidence: 82%
See 3 more Smart Citations
“…However, in apparent contrast to these effects, we found that RU24969 (Acosta et al, 2005) and CP94253 (Pentkowski et al, 2009) dose-dependently decrease cue- and cocaine-primed reinstatement of extinguished cocaine-seeking behavior. The RU24969-induced decreases in reinstatement of cocaine seeking are reversed by the antagonist GR127935, suggesting that they are 5-HT 1B R-mediated.…”
Section: Dysregulation Of 5-ht1brscontrasting
confidence: 82%
“…As summarized in Table 5, Parsons et al (1998) subsequently showed that the more selective 5-HT 1B R agonists RU24969, CP94253 and CP93129 produce a similar effect on cocaine SA, and that the effect of CP94253 is reversed by the 5-HT 1B/1D R antagonist GR127935. These findings have been replicated by two other laboratories (Pentkowski et al, 2009; Przegalinski et al, 2007). Furthermore, we found that viral enhancement of 5-HT 1B R expression in terminals of medial NAc sh neurons shifts the dose– effect function for cocaine SA upward and to the left under a low demand reinforcement schedule (Pentkowski et al, 2012a).…”
Section: Dysregulation Of 5-ht1brssupporting
confidence: 58%
See 2 more Smart Citations
“…Investigações utilizando técnicas farmacológicas e genéticas sugeriram envolvimento do receptor 5-HT 1B na vulnerabilidade ao abuso de drogas, como ingestão de etanol e cocaína, provavelmente através de uma ação indireta no sistema dopaminérgico (Hoplight, Sandygren e Neumaier, 2006;Pentkowski et al, 2009 (Aghajanian e Marek, 1999).…”
Section: Sistema Serotoninérgico E Comportamentos Emocionaisunclassified